Integrating river basin DSSs with model checking. - Gallardo-Melgarejo, María del Mar; Merino-Gómez, Pedro; Panizo-Jaime, Laura; Salmerón Moreno, Alberto (Springer, 2017)
This paper presents a Decision Support System (DSS) based on formal methods for the management of complex river basins in flood scenarios. The DSS is the result of integrating two different DSSs. First, a DSS for dam management that uses the \spin model checker to produce the manoeuvres and the discharged water over time to satisfy user-defined constraints. Second, a DSS that performs numeric simulations of rainfall and water flow along the river basin, taking into account the water discharged by dams. By integrating these two DSSs, the user can define constraints over the parameters of the river basin and all the dams. We use \spin to find the sequences of dam manoeuvres that mitigate the effect of floods along the river basin, according to these constraints. This work is part of the SAID project, a European demonstration project whose main goal is to smartly manage river basins by means of the integration of different DSSs. The demonstrator basin is the Guadalhorce river basin, located in the south of Spain. We apply the method to develop a DSS for this river basin in particular, but the approach is general enough that it can be applied to any river basin.
Keywords: Cuencas hidrográficas - Gestión; Inundaciones - Control; Sistemas de soporte a la decisión; Métodos formales (Informática); Decision support system; Basin management; Formal methods